Kontribusi Remunerasi, Lingkungan Kerja dan Kompetensi terhadap Kinerja Pegawai pada Fakultas Kedokteran Universitas Pendidikan Ganesha - I.K. Sumardana; I.G.K.A. Sunu; I.N. Natajaya (Jurnal Administrasi Pendidikan Indonesia, 2022)
This study aims to determine the magnitude of the effect of remuneration, work environment, and competence on employee performance in the Faculty of Medicine, Ganesha University of Education. This study uses an "ex-post facto" approach involving 36 employees of the Faculty of Medicine, Ganesha University of Education. The data collection method used is a questionnaire regarding data on remuneration, work environment, and employee competence and performance. In conducting data analysis for this research, it was carried out in three stages, namely the data description stage, the analysis requirements testing stage, and the hypothesis testing stage. The research results obtained are that there is an influence between remuneration, work environment, and competence on performance partially or simultaneously.